Epidemiology of childhood injuries in Saudi Arabia: a scoping review - Hadeel Albedewi; Nouf Al-Saud; Abdulhameed Kashkary; Ada Al-Qunaibet; Salem M. AlBalawi; Suliman Alghnam (BMC, 2021)
Abstract Background Injury is the leading cause of death among Saudi children. Despite that, much remains unknown on the epidemiology and the extent of burden. This scoping review aims to describe previous literature on injury burden, including types, causes, and outcomes. Methods We conducted a scoping literature search of English published articles on injuries among Saudi children between 0 to 18 years old using Scopus, MEDLINE, and Web of Science between January 2000 and December 2020. The primary outcome was the type and the cause of childhood injuries. Data extraction was based on specified data elements that included study characteristics and epidemiological parameters. The STROBE checklist was used to assess the quality of publications. Results The initial review identified 3,384 studies. Of which, 36 studies met the inclusion criteria. A total of 20,136 children were included; of them, 69% were males. Among studies that examined overall injuries, falls represented 31.9%, while 25.1% were due to Motor Vehicle Collision (MVC). The leading cause of fractures was falls (37.9%), followed by MVC (21.5%). The leading cause was flames (52.1%) followed by scald (36.4%) for burns. While for poisoning, medications were the leading cause of (39.9%), followed by toxic household products (25.7%). Weighted mortality rates were 5.2% for overall injuries, 8.3% for fractures of the skull and spine, and 17.4% for burns. Conclusions MVC and falls are associated with the highest share of injuries in the kingdom. These findings can guide prevention efforts to reduce injury burden and improve population health. Further population-based research is warranted to explore the determinants of childhood injuries across all regions of Saudi Arabia.